Tri-Axial Shear Tests on Hydrate-Bearing Sediments during Hydrate Dissociation with Depressurization - Dongliang Li; Qi Wu; Zhe Wang; Jingsheng Lu; Deqing Liang; Xiaosen Li (Energies, 2018)
A series of tri-axial shear tests were carried out to determine the stress and strain characteristics, as well as the volume deformation of methane hydrate-bearing sediments during gas hydrate dissociation. An innovative type of depressurization was adopted with a high-pressure and low-temperature tri-axial apparatus. Results show that: (1) decrease in pore pressure during the shear process may result in the failure of hydrate-bearing sediments, but they did not collapse completely due to high effective confining pressure; (2) depressurization leads to the contraction of volumetric strain and the ultimate deformation shows no difference compared to that prior depressurization; (3) high saturation hydrate-bearing sediments were more sensitive to depressurization, which could be due to the methane hydrate acting as a skeleton structure at some sites when the pore hydrates’ saturation is high.